Application of Fuzzy Logic Mamdani Method to Determine the Amount of Ayudes Production (Case Study: CV. Abadi Tiga Mandiri Ambon) - Rumalowak, Diana; Lesnussa, Yopi Andry; Rumlawang, Francis Yunito (Pattimura University, 2023)
A company does not see a problem, namely level competition. This competition is for companies to be able to provide a marketing or productivity strategy in order to survive and even have to increase their production volume. Because the estimated number of products produced is less than the number of requests, the company will lose the opportunity to get maximum and somewhat profit. Therefore, what needs to be considered in deciding the total of production is the total of demand and supply date. Writing and discussion in this study is about the application of the Logic Fuzzy Method Mamdani (Min-Max) to determine the total of production based on the total of demand and supply where the data is taken from CV. Abadi Tiga Mandiri Ambon and by applying the fuzzy logic method mamdani and Matlab assistance obtained results with a truth level of 93,238%. So that the application of Mamdani's Fuzzy Logic Method can help companies determine the number of items that must be made.